Endocrinal assessment of chronic obstructive pulmonary disease patients as compared to control groups - Toppo, Amardeepak; Sudheer, D.; Rajawat, G. S.; Kurian, Thomas (International Journal of Research in Medical Sciences, 2017)
Background: Hormones also take part in respiratory control via peripheral chemo receptors or by their local effects on the lungs and the airways. In chronic obstructive pulmonary disease patients, respiratory muscles are required to work efficiently than normal individuals to establish a sufficient respiration. Changes in serum hormone levels of COPD patients adversely affect functioning of respiratory muscles. Objective of the study was to assess endocrinal profile in COPD patient with comparable control groups. Methods: A Hospital based Case control study conducted at Department of Pulmonary Medicine, Late B.R.K.M Government Medical College, Jagdalpur, Chhattisgarh, India during July 2016 to January 2017. Study included 75 diagnosed cases of COPD in which moderate, severe, very severe COPD was 25 in each of this group (per GOLD ‘s guideline) and compared to age matched 25 healthy control. Results: In this study serum growth hormone and serum testosterone showed significant difference between COPD cases and control group and fair significant difference in serum FSH between COPD cases and control groups. There was no significant correlation between serum growth hormone, serum testosterone and serum FSH with COPD grading. There was no statistically difference observed in serum LH (p=0.425) level between COPD cases and control groups. Present study showed there was statistically difference in FT3, FT4 and TSH level between COPD cases and control groups. There was significant negative correlation between FT4 levels between COPD grading. But no correlation seen between COPD grading and control with respect to serum FT3 and TSH level. Conclusions: Endocrinal assessment in present study showed significant decrease in serum growth hormone and serum testosterone in COPD patients, which are anabolic hormones. Early detection and correction of such an anabolic hormonal abnormality may prevent skeletal and diaphragmatic muscle weakness, and improve respiratory drive of COPD patients.